New genus and species of short-tailed whipscorpion (Schizomida: Hubbardiidae) from the Venezuelan Amazon - Colmenares, Pío A.; Moreno-González, Jairo A.; Villarreal, Osvaldo; Prendini, Lorenzo (Zootaxa, 2025)
A new genus and species of short-tailed whipscorpion (Schizomida: Hubbardiidae Cook, 1899) is described based on specimens collected in the Venezuelan state of Amazonas. The new genus differs from other Neotropical genera in the presence of six setae on opisthosomal tergite II, the absence of seta Dm4 on the flagellum in both sexes, the female flagellum comprising four segments, and the median lobes of the spermatheca being four times longer than the lateral lobes. Jipai longevus gen. et sp. nov. increases the count of South American schizomid genera to fourteen and the count of species to 57. The type locality of the new taxon is situated in the Guiana region of Amazonia s. l., where three other hubbardiid genera have also been recorded. This discovery contributes to the understanding of Amazonian schizomid diversity and highlights the need for further sampling in this diverse, vulnerable and poorly explored area.